An Empirical Analysis of Student Satisfaction with Lecturer Teaching Quality: Applying the Expectation-Disconfirmation Theory - Chandra, Dicky; Fitriyanto, Arief (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This study explores the gap between student expectations, actual experiences, and satisfaction with the quality of teaching at the Faculty of Economics and Business at Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA). The research is guided by Expectation-Disconfirmation Theory (EDT) and aims to evaluate the alignment of teaching quality with student expectations. Using a quantitative approach, data were collected through questionnaires distributed to 1,731 students, with 261 responses analyzed. Descriptive statistics, gap analysis, and multiple regression were employed to analyze the data. The findings reveal that actual experiences significantly impact student satisfaction, with key gaps identified in lecturers' subject knowledge, openness to student input, and clarity in material delivery. Recommendations are made for improving pedagogical skills and aligning teaching methods with student needs.